طريقة الوحدة في تعليم اللغة العربية - Dian Ekawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Arabic lesson, as one of international languages, is important to learn. There are four skills to implement in learning the Arabic language, that is : listening, speaking, reading, and writing. To cover those four skills of lerning,the method of unity ( thoriqoh wahdah ) is a right choice to use. There are three aspects in implementing this method, namely: individual, education, and language. Thoriqoh Wahdah is a method of learning that allows students to freely choose the available title them to talk in Arabic, to teach other about the title they have chosen. Further more, students record all the new vocabullary they found in the discourse and compose free essay as the final phase of method. This activity remains under the supervision of teacher.